2012
DOI: 10.1016/j.gie.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, prospective, randomized study of selective bile duct cannulation performed by multiple endoscopists: the BIDMEN study

Abstract: Background: Wire-guided cannulation (WGC) with a sphincterotome for selective bile duct cannulation (SBDC) has been reported to have a higher success rate and lower incidence of post-ERCP pancreatitis (PEP) than conventional methods in some randomized controlled trials (RCTs) that were both single-center and limited to only a few endoscopists.Objective: To estimate the difference in SBDC according to the method and catheter used in a multicenter and multi-endoscopist study. Design:A prospective multicenter RCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 21 publications
(42 reference statements)
3
85
0
1
Order By: Relevance
“…In prospective multicenter clinical studies in Japan, the rate of post-ERCP pancreatitis in high-risk and unselected subjects has been reported to be 11.3% and 3.5%, respectively. 21,22 These rates are similar to those reported in other ethnic groups. 23,24 In addition, one of the major causes of post-metallic stent placement pancreatitis is the occlusion of the pancreatic orifice.…”
Section: Discussionsupporting
confidence: 87%
“…In prospective multicenter clinical studies in Japan, the rate of post-ERCP pancreatitis in high-risk and unselected subjects has been reported to be 11.3% and 3.5%, respectively. 21,22 These rates are similar to those reported in other ethnic groups. 23,24 In addition, one of the major causes of post-metallic stent placement pancreatitis is the occlusion of the pancreatic orifice.…”
Section: Discussionsupporting
confidence: 87%
“…Several randomized studies, systematic reviews, and meta-analyses have reported that WGC is superior to conventional techniques in terms of both the success rate and the incidence of PEP [1][2][3][4][5][6][7][8]. On the other hand, two RCTs from Japan showed no statistically significant difference between the two techniques [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Although wire-guided cannulation was found to significantly shorten cannulation and fluoroscopy times, it did not decrease the incidence of PEP. 9 Another prospective comparative-intervention single-center study of 1249 patients found no significant difference in the rate or severity of PEP between the guidewire and contrast-assisted groups. In fact, there was actually a trend toward increased risk of pancreatitis in the guidewire-assisted group, but the risk of severe pancreatitis occurred more often in the contrast injection group.…”
Section: Guidewire-assisted Cannulationmentioning
confidence: 97%